Does an Elastic Compression Bandage Provide Any Benefit After Primary TKA? - Matthews, Christopher N. (Clin Orthop Relat Res, 2018)
BACKGROUND: Compression bandages often are used after TKA to reduce swelling. However, the degree to which they are helpful has not been well characterized. QUESTIONS/PURPOSES: The purpose of this study was to determine whether use of a compression bandage after TKA was associated with (1) less leg swelling (our primary endpoint); or (2) secondary study endpoints, including improved ROM of flexion and extension, lower visual analog scale (VAS) pain scores for worst pain and pain during physical therapy just before surgery, postoperative day (POD) 1, POD 2, and POD 28, or fewer wound complications within 90 days of surgery. METHODS: A prospective, single-center, two-arm, parallel-group randomized controlled trial was conducted on 51 patients undergoing simultaneous, bilateral, primary TKA between February 2015 and August 2016. Patients were excluded if they had a body mass index > 40 kg/m(2), a history of a venous thromboembolic event, an allergy to the dressing or compression bandage, or lymphedema in one or both legs. Participants averaged a mean age of 62 years (range, 40-83 years). In all patients, we released the tourniquet after full wound closure, and we applied an Aquacel dressing to both limbs. Patients were randomized by opaque envelope, and the compression bandage was applied to the randomized limb. For each leg, study personnel not involved in patient care measured the patients’ limb circumference (thigh, knee, and tibia), ROM, and VAS pain scores 24 hours after surgery, 48 hours after surgery, and on POD 28. The minimal clinically important difference for circumference was 2 cm with a SD of 2 cm in the circumference. For VAS, it was 2 points with a SD of 2. For ROM, it was 10° with a SD of 15. We conservatively picked an effect size of 0.5 SD and assumed a correlation between limbs of 0.3. This set the power level at 0.80 with an α error of 0.05; thus, a power analysis for paired t-tests indicated that 45 patients would be an appropriate sample size. There were 29 patients randomized to the right leg group and 22 patients randomized to the left leg group. There were no differences between the limb with and without the compression bandage preoperatively. RESULTS: Postoperatively, there were no differences between the groups in terms of leg swelling at the thigh (POD 1: mean ± SD = 51 ± 6 with compression bandage versus mean ± SD = 51 ± 6 without compression bandage, mean Δ = - 0.14, 95% confidence interval [CI], -0.65 to 0.37], p = 0.586; POD 2: mean ± SD = 53 ± 6 with compression bandage versus mean ± SD = 53 ± 7 without compression bandage, mean Δ = -0.22, 95% CI, -0.95 to 0.51, p = 0.548; POD 28: mean ± SD = 47 ± 6 with compression bandage versus mean ± SD = 47 ± 6 without compression bandage, mean Δ = -0.01, 95% CI, -0.39 to 0.38, p = 0.975), knee (POD 1: mean ± SD = 45 ± 4 with compression bandage versus mean ± SD = 45 ± 5 without compression bandage, mean Δ = -0.44, 95% CI, -1.16 to 0.28, p = 0.223; POD 2: mean ± SD = 46 ± 4 with compression bandage versus mean ± SD = 46 ± 4 without compression bandage, mean Δ = -0.30, 95% CI, -0.69 to 0.10, p = 0.137; POD 28: mean ± SD = 42 ± 5 with compression bandage versus mean ± SD = 42 ± 5 without compression bandage, mean Δ = 0.21, 95% CI, -0.34 to 0.76, p = 0.446), and shin (POD 1: mean ± SD = 40 ± 4 with compression bandage versus mean ± SD = 40 ± 4 without compression bandage, mean Δ = -0.22, 95% CI, -1.23 to 0.79, p = 0.659; POD 2: mean ± SD = 41 ± 4 with compression bandage versus mean ± SD = 41 ± 4 without compression bandage, mean Δ = -0.31, 95% CI, -0.72 to 0.09, p = 0.126; POD 28: mean ± SD = 37 ± 4 with compression bandage versus mean ± SD = 37 ± 4 without compression bandage, mean Δ = -0.34, 95% CI, -0.92 to 0.24, p = 0.246). There were no differences between the groups in terms of flexion ROM (POD 1: mean ± SD = 56 ± 25 with compression bandage versus mean ± SD = 58 ± 22 without compression bandage, mean Δ = -2.63, p = 0.234; POD 2: mean ± SD = 64 ± 20 with compression bandage versus mean ± SD = 63 ± 23 without compression bandage, mean Δ = 1.22, p = 0.534; POD 28: mean ± SD = 101 ± 20 with compression bandage versus mean ± SD = 102 ± 20 without compression bandage, mean Δ = -1.64, p = 0.103) and extension (POD 1: mean ± SD = 12 ± 7 with compression bandage versus mean ± SD = 12 ± 7 without compression bandage, mean Δ = 0.51, p = 0.328; POD 2: mean ± SD = 9 ± 5 with compression bandage versus mean ± SD = 10 ± 6 without compression bandage, mean Δ = -1.28, p = 0.061; POD 28: mean ± SD = 6 ± 14 with compression bandage versus mean ± SD = 4 ± 4 without compression bandage, mean Δ = 2.19, p = 0.252). With the numbers available, we observed greater maximal postoperative pain for the limb with the compression bandage than the control limb on POD 1 and POD 2, but not on POD 28 (POD 1: mean ± SD = 8 ± 3 with compression bandage versus mean ± SD = 7 ± 3 without compression bandage, mean Δ = 0.66, p = 0.030; POD 2: mean ± SD = 7 ± 2 with compression bandage versus mean ± SD = 7 ± 3 without compression bandage, mean Δ = 0.80, p = 0.008; POD 28: mean ± SD = 4 ± 3 with compression bandage versus mean ± SD = 3 ± 3 without compression bandage, mean Δ = 0.14, p = 0.526). Likewise, there was greater pain during physical therapy for the limb with the compression bandage than the limb without on POD 2, but not on POD 1 and POD 28 (POD 1: mean ± SD = 7 ± 3 with compression bandage versus mean ± SD = 6 ± 3 without compression bandage, mean Δ = 0.29, p = 0.460; POD 2: mean ± SD = 8 ± 2 with compression bandage versus mean ± SD = 7 ± 3 without compression bandage, mean Δ = 0.67, p = 0.018; POD 28: mean ± SD = 5 ± 2 with compression bandage versus mean ± SD = 5 ± 3 without compression bandage, mean Δ = 0.14, p = 0.600). With the numbers available, we observed no difference in 90-day wound healing complications between the limb with and the limb without the compression dressing; however, the sample size was too small to analyze this in a meaningful statistical way. Overall, there were 6% total wound complications in the compression bandage group and 12% total wound complications in the group without the compression bandage (odds ratio [OR], 0.47; p = 0.487). Drainage was not observed in the group with the compression bandage, whereas the group without the compression bandage had 6% drainage (OR, 0.00; p = 0.243). There were no deep infections or reoperations within 90 days postoperatively. CONCLUSIONS: Applying a compression bandage after TKA did not result in any clinical improvement in limb circumference, ROM, or pain. Based on this study, we believe that applying a compression bandage after TKA neither benefits nor harms the patient. Thus, we no longer use compression dressings for routine primary TKA. LEVEL OF EVIDENCE: Level I, therapeutic study.